The Clinical Impact of Proton Pump Inhibitors When Co-Administered With Dual Antiplatelet Therapy in Patients Having Acute Myocardial Infarction With Low Risk of Gastrointestinal Bleeding: Insights From the China Acute Myocardial Infarction Registry - Shi, Wence; Ni, Lin; Yang, Jingang; Fan, Xiaoxue; Yu, Mei; Yang, Hongmei; Yu, Mengyue; Yang, Yuejin; , China Acute Myocardial Infarction (CAMI) Registry study group (Frontiers in Cardiovascular Medicine, 2021)
Background: The latest guidelines recommend the use of proton pump inhibitors (PPIs) to minimize gastrointestinal bleeding (GIB) in patients receiving dual antiplatelet therapy (DAPT), even though this co-administration may increase the risk of ischemia due to drug interactions. We have noticed that there are few studies conducted on patients with a lower risk of GIB. Therefore, we investigated the clinical effect of co-administration of PPI on DAPT patients with low GIB risk. Methods and Results: From January 2013 to September 2014, a total of 17,274 consecutive patients on DAPT from 108 hospitals with low risk for GIB in the China Acute Myocardial Infarction (CAMI) registry were analyzed. The primary endpoints were GIB and major adverse cardiovascular and cerebrovascular events (MACCE). Multivariate logistic regression analysis and Cox proportional hazard models were used to assess the effect of PPIs use. Of the analyzed patients, 66.6% (n = 11,487) were treated with PPIs. PPI use did not show an extra gastrointestinal protective effect in patients with low risk for GIB who were hospitalized and on follow-up after 2 years. Moreover, it was associated with an increased risk of stroke during the 2-year follow-up [hazard ratio (HR) 2.072, 95% confidence interval (CI) 1.388–3.091, p = 0.0003] and an increased risk of MI after 6 months (HR 1.580, 95% CI 1.102–2.265, p = 0.0119). We found the same results after propensity score matching. Conclusion: PPI use is prevalent in DAPT patients with low GIB risk. PPIs did not show an extra gastrointestinal protective effect, while an increased risk of stroke was observed during the 2-year follow-up. Clinical Trial Registration:www.clinicaltrials.gov, identifier NCT01874691.